Prevalence of Hepatitis B and C Viral Infections in Chronic Liver Disorder - Mariam Riaz, Henna Khalid, Nazma Kiran (Pakistan Journal of Medical & Health Sciences, 2022)
Background and aim: Hepatitis is a liver infection caused by a variety of viruses and is a major public health issue worldwide. Hepatitis B and C are common liver infections caused by HBV and HCV that spread through sexual contact, contaminated blood product and contaminated needles. The present study aimed to determine the prevalence of hepatitis B and C in chronic liver disorders. Material and Methods: This prospective study was conducted on 136 chronic liver disease patients in the Department of Gastroenterology and Hepatology, Ayub Teaching Hospital Abbottabad from August 2021 to January 2022. Patients above 18 years age and clinically diagnosed with chronic liver disorder were enrolled. Chronic liver disorders were diagnosed based on clinical history, impaired liver function tests, and ultrasound. A questionnaire was used to accumulate possible related factors with virus infections from patients. Qualitative immunochromatographic method was used for screening out the serum for the presence of anti-hepatitis C virus antibodies and hepatitis B surface antigen. SPSS version 26 was used for data analysis. Results: Out of 136 chronic liver disorders, there were 88 (64.5%) male and 48 (35.5%) females. The overall mean age was 42.6±6.82 years with an age range from 15 to 75 years. Of the 136 CLD, the single, married, divorced, and widow were 34 (25%), 80 (58.8%), 12 (8.8%), and 10 (7.4%) respectively. The urban and rural dwellers were 98 (72.1%) and 38 (27.9%) respectively. The prevalence of Hepatitis B surface antigen and anti-HCV antibody was 52 (38.2%) and 34 (25%) respectively. The incidence of dual HBV and HCV coinfection was 6 (4.4%). Conclusion: The present study found that the prevalence of HBV and HCV infections were 38.2% and 25% among chronic liver disorders. HCV infections were 2.95 times higher in health facilities where dental extractions were provided compared to those who had no dental extraction facilities. All the CLD clinically diagnosed should be tested for HBV and HCV infections. Sterilization of surgical and dental instruments in proper way must be done along with public education regarding infections and transmission modes to prevent infections spreading. Keywords: HBV, HCV, Chronic liver disorders